Family caregivers’ experiences of caring for COVID-19 infected relatives at home: A qualitative study in Shiselweni, Eswatini - Masilela, Thamsanqa G.; Nhlabatsi, Thulani Ricardo (Diversity: Disease Preventive of Research Integrity, 2026)
The emerging literature on COVID-19 has increasingly recognized families as essential care units, yet limited evidence documents how untrained family caregivers experienced home-based care during acute infection in low-resource settings, and how culturally grounded values may inform caregiver support. This study aimed to describe the lived experiences of family caregivers of COVID-19 patients in the Shiselweni region of Eswatini. A qualitative descriptive phenomenological design was employed among ten purposively selected family caregivers, with the final sample size determined by data saturation. Data were collected through in-depth face-to-face, audio-recorded interviews using a pre-tested SiSwati semi-structured interview guide, then analyzed thematically following Colaizzi’s descriptive method. Trustworthiness was strengthened through forward–backward translation and dual coding, and the study adhered to relevant ethical principles. Five themes emerged: (1) emotional and psychological responses to COVID-19 infection, (2) family challenges brought by COVID-19, (3) family support resources, (4) coping with the challenges of COVID-19, and (5) family-perceived caregiving support needs. Findings indicate that caregivers faced substantial emotional and psychological burdens amid fear of infection, limited competence, and inadequate protective equipment. Public health responses should prioritize home-care packages that combine caregiver training, provision of personal protective equipment, and accessible consultation channels; these can be strengthened through islamic ethical principles of rahmah (compassion), amanah (responsibility), and mutual support to protect caregiver wellbeing and family resilience